2009
DOI: 10.1016/j.radonc.2009.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical changes in the pharyngeal constrictors after chemo-irradiation of head and neck cancer and their dose–effect relationships: MRI-based study

Abstract: Purpose-Dysfunction of pharyngeal constrictors (PCs) after chemo-irradiation of head and neck (HN) cancer has been proposed as major cause of dysphagia. We conducted prospective MRI study to evaluate anatomical changes in the PCs after chemoirradiation, to gain insight of the mechanism of their dysfunction and their dose-effect relationships. The PCs were compared to the sternocleidomastoid muscles (SCMs), which receive high doses but do not relate to swallowing.Patients and Methods-Twelve patients with stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 29 publications
(34 reference statements)
6
82
0
1
Order By: Relevance
“…Whilst the notion of the general resistance of skeletal muscle to RT is well-accepted [55], it has been postulated that the PHYSIOLOGICAL SWALLOWING DEFICITS FOLLOWING (C)RT FOR HNC 13 pharyngeal constrictor and laryngeal adductor muscles and epiglottic walls, which are situated in close proximity to the submucosa, may be secondarily affected by the acute radiation-induced inflammatory response of these mucosal layers, culminating in the loss of elasticity and therefore dysfunction of the laryngeal and oropharyngeal musculature [32,56].…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the notion of the general resistance of skeletal muscle to RT is well-accepted [55], it has been postulated that the PHYSIOLOGICAL SWALLOWING DEFICITS FOLLOWING (C)RT FOR HNC 13 pharyngeal constrictor and laryngeal adductor muscles and epiglottic walls, which are situated in close proximity to the submucosa, may be secondarily affected by the acute radiation-induced inflammatory response of these mucosal layers, culminating in the loss of elasticity and therefore dysfunction of the laryngeal and oropharyngeal musculature [32,56].…”
Section: Discussionmentioning
confidence: 99%
“…Besides adaptive implications, the present data provide insights on the pathophysiology of the damage induced by RT. The swelling of both the CM and the L a few months after the end of RT has been documented (18)(19)(20). Investigators at the University of Michigan showed an increase in thickness of the retropharyngeal space by CT 3 months after chemoradiotherapy (18).…”
Section: Discussionmentioning
confidence: 99%
“…All these abnormalities can be responsible for an altered swallowing process and for a post-swallowing residue in the oropharynx, valleculae and hypo-pharynx, which may subsequently be aspirated. Radio-induced dysphagia can often be associated to altered sensitivity, which may cause a silent aspiration and deficient cough reflex [15,[70][71][72][73][74].…”
Section: Simulation Computerized Tomography (S-ct)-basedmentioning
confidence: 99%